Increase in incidence of invasive pneumococcal disease caused by serotype 3 in children eight years after the introduction of the pneumococcal conjugate vaccine in Hong Kong. Issue 2 (1st February 2019) - Ho, Pak-Leung; Law, Pierra Ying-Tung; Chiu, Susan S.
ABSTRACT: This study used several datasets of reported and serotyped invasive pneumococcal disease (IPD) cases to estimate vaccine and non-vaccine type incidence in Hong Kong children. Incidence was analyzed by four time periods to indicate pre-PCV (period 1, 1995–2004), private market only (period 2, 2006–2009), and following early (period 3, 2010–2014, mixed use of 7-, 10- and 13-valent vaccines) and more than five years (period 4, 2015–2017, 13-valent vaccine only) of routine implementation (since September 2009). IPD incidence decreased by 85% and 35% in aged < 2 years and aged 2 to < 5 years, respectively, from period 1 to period 4. This was due to a 97% reduction in the serotypes covered by 7-valent vaccine. In period 4, 59% of the disease was caused by serotype 3 and was largely attributed to an ermB positive, novel ST6011 clone. The finding corroborates an increasing body of evidence that the efficacy of the 13-valent vaccine against infection by this serotype is low.